Uji Beda Efektivitas Ekstrak Biji Rambutan Dengan Ektrak Biji Mangga Terhadap Mortalitas Larva Nyamuk Aedes aegypti - Rien Kusuma Hatmoko; Diah Karunia Binawati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2019)
The use of chemical larvicides to control mosquito larvae in water reservoirs has a negative impact, causing environmental pollution and resistance to target organisms. The alternative to reduce this impact is using vegetable larvacides from Rambutan Seeds (Nephelium Lappaceum L) and Mango Seeds (Mangifera indica L). This study aims to determine the effectiveness of Rambutan Seed Extract (Nephelium Lappaceum L) and Mango Seed Extract (Mangifera indica L) on the mortality of Aedes aegypti larvae after being treated for 24 hours. This type of research is experimental with a pure experimental study design (true experiment). The treatment concentration given for 24 hours was 0, 2%, 4%, 6%, 8% of each extract with 5 replications. The samples in the study were III instar Aedes aegypti larvae totaling 800 heads. Data analysis was performed by Anova test and probit test. Based on the results of research on rambutan seed extract (Nephelium lappaceum L) LC50 value of 3.190% was more effective against mortality of Aedes aegypti larvae than Mango seed extract (Mangifera indica L) LC50 value of 4.758%. Keywords: Rambutan Seeds (Nephelium Lappaceum L), Mango Seeds (Mangifera indica L), mortality of Aedes aegypti larvae.